The Perceptions of Society toward the English Course at Lembang Kole - Rachel Rachel (Publikasi dan UKI Press UKI Toraja., 2019)
The objective of this research is to find out the perceptions of society toward English course at Kole Barebatu. In this research, the writer used quantitative descriptive method. The population of this research is the the society at Kole Barebatu, there were 844 people consists of 425 male and 419 female. The writer used stratified sampling because the number of object is relatively large. The writer took 31 societies as respondent. The writer choose the representatives of student, office staff, teacher, housewife, bussinesman, farmer, unemployment, and government as respondent. In collecting data, the writer used questionnaire to find out the perceptions of the society toward English Course at Kole Barebatu. The result shows that there are positive perceptions and negative perception from the society of English course at Lembang Kole Barebatu. The positive perception more dominant than negative perception. The positive perceptions such as, the society said agree with English course is important to learn, one of the way to get English knowledge is by a English Course, and can help the society to get a job in the future. The negative perception is the society is disagree if one of the tutors is a student. It means English course that the local government conducted at Kole Barebatu is very exemplary program and it can help the society to get a English knowledge.